RAPID AND SENSITIVE LC-MS/MS METHOD FOR THE ANALYSIS OF ALLOPURINOL IN HUMAN PLASMA - V.V.RAMI REDDY; K. HUSSAIN REDDY (International Journal of Pharma and Bio Sciences, 2015)
A rapid and highly sensitive liquid chromatography/tandem mass spectrometric (LC/MS/MS) method for determination allopurinol (AP) in human plasma was developed. The analyte and internal standard (IS), Ganciclovir-d5, were extracted from human plasma via liquid/liquid extraction (LLE) with ethyl acetate (2.5mL), supernatant was dried and reconstituted in 200 µL of 10mM ammonium acetate-methanol (80:20 V/V) solution and separated on an Waters Symmetry Shield, RP8, 3.5µm, 4.6 x 100mm within 4 min. Quantification was by multiple reaction monitoring (MRM), where the acquired mass for allopurinol and IS are m/z 136.7→110.2 and 261.1→151.8 respectively. The assay was validated with linear range of 50–3000 ng/mL. The intra- and interday precisions (RSD %) were within 1.71 to 10.34% and 3.79 to 7.43% respectively. This method is suitable for the quantification of AP in human plasma for real sample analysis.